CMV MANAGEMENT WITH SPECIFIC IMMUNOGLOBULINS: A MULTICENTRIC RETROSPECTIVE ANALYSIS ON 92 ALLOTRANSPLANTED PATIENTS. - Michele Malagola; Raffaella Greco; Stella Santarone; Anna Paola Iori; Luisa Quatrocchi; Walter Barberi; Bruzzese Antonella; Salvatore Leotta; Alessandra Carotti; Antonio Pierini; Simon Bernardi; Enrico Morello; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
CMV represents one of the most serious life-threatening complications of allogeneic stem cell transplantaion (allo-SCT). Pre-emptive treatment is highly effective, but toxicity and repetitive reactivation of CMV represent a major challenge in the clinical practice. The use of anti-CMV specific immunoglobulins (Megalotect) is controversial.